Cover Picture: Plasma Process. Polym. 4∕2016. Issue 4 (April 2016) - Fanelli, Fiorenza; Fracassi, Francesco
Abstract : Front Cover: Fluorocarbon coatings are deposited on opencell polyurethane foams using an atmospheric pressure dielectric barrier discharge fed with helium and hexafluoropropene. The discharge is ignited both outside and inside the three‐dimensional porous structure of the foam, so that thin film deposition can be achieved on both its outer and inner surfaces. Further details can be found in the article by F. Fanelli and F. Fracassion page 470 .